Analysis of Arabic Language Difficulties of STDI Imam Syafi'i Jember Students: A Case Study of Islamic Family Law Study Program - Ahmad Dzakwan Irfani; Muhammad Rizal Shalahuddin (Golden Ratio of Data in Summary, 2026)
This study analyzes the difficulties of learning Arabic among students of the Islamic Family Law Program at STDI Imam Syafi’i Jember and identifies the factors influencing these difficulties. Using a qualitative case study approach, data were collected through semi-structured interviews, participant observation, and documentation involving students, Arabic lecturers, and academic staff. Informants were selected through purposive and snowball sampling techniques. The findings reveal that students experience difficulties in understanding qawaid (Arabic grammar and morphology), mastering vocabulary, and reading Arabic texts. Psychological barriers, particularly low self-confidence in using Arabic, also hinder learning. In addition, differences in educational backgrounds and the lack of an Arabic-speaking environment significantly affect students’ learning processes. This study contributes theoretically to qualitative research on Arabic language learning and provides practical recommendations for Islamic higher education institutions to develop more contextual and adaptive Arabic learning strategies suited to students in Sharia-related study programs.